2019
DOI: 10.1017/s0033291719002770
|View full text |Cite
|
Sign up to set email alerts
|

Using network analysis to examine links between individual depressive symptoms, inflammatory markers, and covariates

Abstract: Background Studies investigating the link between depressive symptoms and inflammation have yielded inconsistent results, which may be due to two factors. First, studies differed regarding the specific inflammatory markers studied and covariates accounted for. Second, specific depressive symptoms may be differentially related to inflammation. We address both challenges using network psychometrics. Methods We estimated seven regularized Mixed Graphical Models in the Netherlands Study of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
132
3
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(162 citation statements)
references
References 58 publications
(101 reference statements)
16
132
3
3
Order By: Relevance
“…We found that several structural characteristics (i.e., global strength, expected influence, and symptom-symptom associations) of depression networks are moderated by CRP. This extends previous work that found that CRP is not equally associated with all symptoms of depression (e.g., Fried et al, 2019;Haroon et al, 2016;Jokela et al, 2016;Moriarity et al, 2020a), to demonstrate that differences in CRP might be associated with differences in depression symptom structure. Two of the three group-differences hypotheses were supported, with mixed support for the third.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found that several structural characteristics (i.e., global strength, expected influence, and symptom-symptom associations) of depression networks are moderated by CRP. This extends previous work that found that CRP is not equally associated with all symptoms of depression (e.g., Fried et al, 2019;Haroon et al, 2016;Jokela et al, 2016;Moriarity et al, 2020a), to demonstrate that differences in CRP might be associated with differences in depression symptom structure. Two of the three group-differences hypotheses were supported, with mixed support for the third.…”
Section: Discussionsupporting
confidence: 87%
“…This has led to calls for the inflammatory phenotyping of depression (Felger et al, 2018) and increased modeling of specific symptoms and symptom subtypes in immunopsychiatry . These pursuits have included profiling symptoms associated with inflammation (Fried et al, 2019;Jokela et al, 2016;Kappelmann et al, 2020;Moriarity et al, 2020a) as well as inflammatory proteins and cell counts associated with MDD (Lynall et al, 2020). Although there are many different inflammatory proteins, CRP, an acute phase reactant, arguably is the most widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we recently utilised network analysis to examine the complex interrelations of resilience factors and their relations with mental health symptoms in adolescents reporting childhood adversity [178], addressing the complexity of resilience. Resilient functioning results from complex interactions between multiple bodily systems [179] and network analyses make it possible to examine interactions between different symptoms and neurobiology at an unprecedented level of detail [180]. In sum, recent statistical innovations have the potential to approach questions of resilience using frameworks that fully embrace the complexity inherent in resilience research.…”
Section: Statistical Techniques To Investigate Complexity In Resilienmentioning
confidence: 99%
“…Similarly, there are reports that lowgrade inflammation shows specificity for somatic symptoms of depression (e.g. sleep problems, low energy, or increased appetite) [101][102][103][104], so ongoing studies evaluating immunotherapy as a treatment for depression may benefit from symptom-based treatment allocation rules. We therefore encourage researchers to apply the SOrT metric to other treatment comparisons to evaluate its value as a precision medicine tool.…”
Section: Discussionmentioning
confidence: 99%